Question
upstudy study bank question image url

d) \( \frac{2^{a+1} \cdot 3^{a-1}}{6^{a}} \) g) \( \frac{2^{1+2 n} \cdot 8^{1-3 n}}{4^{n+1}} \) j) \( \frac{(x y z)^{o}}{2^{-3}} \)

Ask by Lowe Wells. in South Africa
Feb 16,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

(d) 2/3 (g) 2^(2–9n) (j) 8·(xyz)^o

Solution

We are given three expressions to simplify. Let’s work through each one step‐by‐step. ───────────────────────────── (d) Simplify  (2^(a+1) · 3^(a–1)) / (6^a) Step 1. Write 6^a as (2·3)^a = 2^a · 3^a. Step 2. Substitute into the original expression:   (2^(a+1) · 3^(a–1)) / (2^a · 3^a) Step 3. Simplify the powers of 2:   2^(a+1) / 2^a = 2^( (a+1) – a) = 2^1 = 2 Step 4. Simplify the powers of 3:   3^(a–1) / 3^a = 3^( (a–1) – a) = 3^(–1) = 1/3 Step 5. Multiply the simplified parts:   2 · (1/3) = 2/3 So, answer (d): 2/3 ───────────────────────────── (g) Simplify  (2^(1+2n) · 8^(1–3n)) / (4^(n+1)) Step 1. Express 8 and 4 as powers of 2:   8 = 2^3  and  4 = 2^2 Step 2. Write 8^(1–3n) as (2^3)^(1–3n) = 2^(3(1–3n)) = 2^(3 – 9n). Step 3. Write 4^(n+1) as (2^2)^(n+1) = 2^(2n+2). Step 4. Now substitute these back:   (2^(1+2n) · 2^(3–9n)) / 2^(2n+2) Step 5. Combine the exponents in the numerator:   2^( (1+2n)+(3–9n) ) = 2^(4 – 7n) Step 6. Now the expression is:   2^(4 – 7n) / 2^(2n+2) = 2^( (4 – 7n) – (2n + 2) ) Step 7. Simplify the exponent:   (4 – 7n) – (2n + 2) = 4 – 7n – 2n – 2 = 2 – 9n So, answer (g): 2^(2–9n) ───────────────────────────── (j) Simplify  ((x y z)^o) / (2^(–3)) Note: Here the exponent “o” is treated as a variable (not the number zero). Step 1. Recognize that dividing by 2^(–3) is the same as multiplying by 2^3:   ((x y z)^o) / (2^(–3)) = (x y z)^o · 2^3 Step 2. Since 2^3 = 8, we have:   8 · (x y z)^o So, answer (j): 8·(xyz)^o ───────────────────────────── Summary of Answers: (d) 2/3 (g) 2^(2–9n) (j) 8·(xyz)^o

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To simplify \( \frac{2^{a+1} \cdot 3^{a-1}}{6^{a}} \), remember that \(6\) can be expressed as \(2 \cdot 3\). Thus, \( 6^a = (2 \cdot 3)^a = 2^a \cdot 3^a \). This allows you to rewrite the denominators and combine the fractions more easily, leading to a neat simplification! For \( \frac{2^{1+2n} \cdot 8^{1-3n}}{4^{n+1}} \), recognize that both \(8\) and \(4\) can be expressed as powers of \(2\): \(8 = 2^3\) and \(4 = 2^2\). Rewriting everything in terms of base \(2\) provides a clear path to simplify the expression while also allowing you to combine the exponents effectively for a final, streamlined result!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy